Knowledge of sexually transmitted diseases and sexual behaviours among Malaysian male youths - Awang, H.; Wong, L.P.; Jani, R.; Low, W.Y. (2013)
Summary This study examines the knowledge of sexually transmitted diseases (STDs) among male youths in Malaysia. A self-administered survey was carried out on a sample of 952 never-married males aged 15-24 years. The respondents were asked about their knowledge of STDs, how these diseases get transmitted and their sexual behaviours. The data showed that 92 of the respondents knew of at least one STD (syphilis, gonorrhoea, chlamydia, herpes, genital warts, yeast infection, trichomoniasis or HIV/AIDS). About 95 of them knew of at least one method of STD transmission. Urban and tertiary-educated male youths showed a substantially higher proportion of awareness of STDs and transmission methods compared with their rural and less-educated counterparts. The data also indicated that 10 of the study sample admitted to having had sexual experiences. There were still a large proportion of the respondents who were not aware of STDs other than syphilis and HIV/AIDS and the means of transmission, such as multiple sex partners, including those who claimed to be sexually active. Thus there is a need for more concerted efforts to disseminate information on STDs and transmission methods to a wider audience in Malaysia, especially youths in rural areas.